Санкт-Петербург: 300 лет истории - Анисимов Е. В.; Балашов Е. М.; Ваксер А. З.; Ганелин Р. Ш.; Дзенискевич А. Р.; Ковальчук В. М.; Купайгородская А. П.; Нардова В. А. (СПб., Наука, 2003)
Санкт-Петербургу 300 лет